2022
DOI: 10.1002/ctm2.758
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 mediates pathologic changes of secondary lymphedema by promoting fibrosis and inflammation

Abstract: TGF-β1 expression, fibroblast proliferation and ECM deposition are increased in lymphedematous skin. • Tissue lysate of lymphedematous skin induces fibroblast proliferation, ECM production and increases the stiffness of fibroblasts, LECs and LSMCs. • Inhibition of TGF-β1 decreases ECM deposition, immune cell infiltration and increases collateral lymphatics formation.• Topical treatment of pirfenidone is highly effective for lymphedema treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 141 publications
1
24
0
Order By: Relevance
“…In this model, histological signs of lymphedema, such as inflammation and fibroadipose deposition, develop 4-6 weeks after skin and lymphatic excision. ( 16, 40 ) We therefore harvested tail skin specimens 2 and 6 weeks after surgery to analyze epidermal changes before and after the onset of lymphedema. ( 40 ) We found that hyperkeratosis occurred rapidly after lymphatic injury and was evident even at the 2-week time point in skin sections harvested 2-3 cm from the excision site ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, histological signs of lymphedema, such as inflammation and fibroadipose deposition, develop 4-6 weeks after skin and lymphatic excision. ( 16, 40 ) We therefore harvested tail skin specimens 2 and 6 weeks after surgery to analyze epidermal changes before and after the onset of lymphedema. ( 40 ) We found that hyperkeratosis occurred rapidly after lymphatic injury and was evident even at the 2-week time point in skin sections harvested 2-3 cm from the excision site ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…( 16, 40 ) We therefore harvested tail skin specimens 2 and 6 weeks after surgery to analyze epidermal changes before and after the onset of lymphedema. ( 40 ) We found that hyperkeratosis occurred rapidly after lymphatic injury and was evident even at the 2-week time point in skin sections harvested 2-3 cm from the excision site ( Fig. 2A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…Noticeably, FN-1 was verified as a crucial gene closely associated with the growth of SFs and has huge potential for regulation of RA initiation. FN-1, an ECM protein produced by fibroblasts, was previously found to be involved in the pathological changes in many tissues ( Liu et al, 2019 ; Baik et al, 2022 ). Furthermore, emerging evidence has revealed that FN-1 is closely related to RA initiation and development ( Przybysz et al, 2007 ; van Beers et al, 2012 ; Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy together with BMI, age, tumor stages, lymph node dissection and the number of lymph nodes removed are the main risk factors for lymphedema after cancer treatment ( Tsai et al, 2009 ; DiSipio et al, 2013 ; Warren et al, 2014 ; Hu et al, 2022 ). Radiotherapy is well known to cause tissue fibrosis, as a result of transforming growth factor TGF-β1 production ( Martin et al, 2000 ; Baik et al, 2022 ). It also affects lymphatic function by inducing lymphatic endothelial cell apoptosis and decreasing the number of cutaneous lymphatic vessels ( Avraham et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%